DUALISME PEMAHAMAN MASYARAKAT NAGARI PASIR TALANG TIMUR SOLOK SELATAN TERHADAP PENCATATAN PERKAWINAN: Abstrak, Pendahuluan, Metode Penelitian, Pembahasan dan Hasil, Kesimpulan, Daftar Pustaka - Wedi Afri; Sulfinadia, Hamda; Efrinaldi (Fakultas Agama Islam UNISMA, 2024)
The aim of this research is to determine the factors causing the dualism of community understanding in Nagari Pasir Talang Timur District. Pagu River District. South Solok regarding marriage registration and to find out the legal efforts taken by the people of Nagari Pasir Talang Timur District. Pagu River District. South Solok regarding unregistered marriages. This research method uses a field research method in the form of qualitative research assisted by direct interviews with people who carry out private marriages and interviews with the KUA, Sungai Pagu District, South Solok Regency. Interviews are carried out by asking detailed questions directly and face to face with the relevant parties. The data sources used in this research are primary data sources and secondary data sources. The results of this research are the factors that cause dualism in the understanding of the people of Nagari Pasir Talang Timur Kec. Pagu River District. South Solok Regarding Marriage Registration, the first thing is that marriage registration does not exist in Islamic law. Second, the community expressed that they obey religion first, then obey state laws and regulations. And third, the legal regulations in Indonesia regarding marriage are different from the teachings of the Islamic religion. The legal action taken by the community against unregistered marriages is first, by registering the marriage through a marriage certificate at the Religious Court. However, this marriage law can be submitted to the Religious Court for reasons of resolving a divorce. Second, carrying out remarriage in accordance with applicable laws and regulations with authorized officials, namely officials from the Office of Religious Affairs (KUA). Keywords: Dualism, Marriage Registration, Private Marriage